2003
DOI: 10.1002/ejoc.200300004
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition Behavior of 1,2‐Thiaphospholes: Reactions with Diazocumulenes and with Cyclopentadiene

Abstract: 1,2-Thiaphospholes 3a,b react with (1-diazo-2-oxoalkyl)silanes 1a−c to form [1,2] ,2]thiaphosphole systems 4 with cis-anti-cis configuration of the tricyclic framework. They are accompanied by small amounts of compounds 5 that are presumably the cis-syn-cis isomers of 4, and 6-alkylidene-1-phospha-2-thiabicyclo[3.1.0]hex-3-enes 6. It is likely that these reactions proceed by [3+2] cycloaddition of diazocumulenes, which coexist with diazo compounds as minor equilibrium components, at the P=C bond of the heterop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The latter undergoes subsequently successive ring expansion and further [4 + 2] cycloaddition either with dicyclopentadiene to form 22 or with cyclopentadiene to produce 23. The structure of 22 was confirmed by X-ray crystal studies [53] (Scheme 9).…”
Section: [4 + 2] Cycloadditionsmentioning
confidence: 81%
See 3 more Smart Citations
“…The latter undergoes subsequently successive ring expansion and further [4 + 2] cycloaddition either with dicyclopentadiene to form 22 or with cyclopentadiene to produce 23. The structure of 22 was confirmed by X-ray crystal studies [53] (Scheme 9).…”
Section: [4 + 2] Cycloadditionsmentioning
confidence: 81%
“…In the case of 62 (R 3 Si = iPr 3 Si), the bicyclic alkylidenephosphi-SCHEME 21 ranes 72 were also isolated in low yields (4-8%). The structure of 70 (R 1 = tBu, R 3 Si = iPr 3 Si, Ar = Ph) was confirmed by X-ray crystal studies [53]. In the reaction of 62 (R 1 = tBu, R 3 Si = iPr 3 Si) with 19 (Ar = Ph), trace amount of 71 was also isolated [53] (Scheme 21).…”
Section: Scheme 20mentioning
confidence: 84%
See 2 more Smart Citations
“…A versatile approach to [a]-fused phosphiranes is provided by the cyclopropanation of the P=C bond of heterophospholes with diazo compounds through a [3+2] cycloaddition/ring-contraction sequence. [10] As 3,5-diaryl-1,2-thiaphospholes are readily available [11] and the P=C bond of 1,2-thiaphospholes is an excellent cycloaddition partner, [12][13][14] we followed this route to synthesize a 6,6-diphenyl-2-thia-1-phosphabicyclo[3.1.0]hex-3-ene using diazodiphenylmethane as the cyclopropanation reagent. [15] We found that the thermal stabilities of both the phosphirane and its W(CO) 5 and Fe(CO) 4 complexes are only moderate, and that the effect of elevated temperatures is different for the free phosphirane and its metal complexes.…”
Section: Introductionmentioning
confidence: 99%